REHABILITATION OF PATIENTS AFTER SURGICAL TREATMENT OF STATIC DEFORMITIES OF THE FOREFOOT - Prozorovskiy, Dmytro; Staude, Volodymyr; Buznytskiy, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Postoperative rehabilitation of patients with hallux valgus is just as important, if not more so, than a technically flawless surgical intervention. Carrying out rehabilitation measures is an integral part of the postoperative period, which must be individual for each patient and depend on the volume and type of surgical intervention, the patient's age, and accompanying pathology. Objective. To improve the results of the recovery of patients after orthopedic surgical interventions on the front part of the foot due to the developed complex system of postoperative rehabilitation. Methods. The article provides an analysis of the results of treatment of 70 patients with transversely spread deformation of the forefoot and hallux valgus 1–2 degrees using different approaches to rehabilitation measures in the postoperative period. The patients were divided into 2 homogeneous groups by age, gender and degree of hallux valgus. Unlike the control group, manual therapy and myofascial massage techniques were additionally used in the main group. The results. The results of the treatment were evaluated according to the AOFAS scoring scale for the forefoot, which is generally accepted in the world. In the preoperative period, the average AOFAS score in the main and control groups was 65.4 and 64.7 points, respectively. 45 days after surgery, the average scores were 74.7 and 74.4 points, respectively. After 60 days, the average score in the main group was 92.1 points, and 82.6 in the control group. 3 months (90 days) after the surgical interventions, the average scores practically coincided in both groups and amounted to 93.7 points in the control group and 95.0 in the main group. The patients of the main group resumed their usual activities after 2 months. after the operation on the front part of the foot, and the control after 3 months. Conclusions. The use of myofascial massage, manual therapy for mobilizing the metatarsophalangeal and interphalangeal joints of the toes with gymnastics to strengthen not only the stabilizers of the foot, but also to restore the bearing capacity of the girdle of the lower extremities and the stereotype of walking, made it possible to obtain not only a positive functional result, but also to speed up the recovery compared to the control group per month.